2020
DOI: 10.1021/acs.inorgchem.0c03249
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Spectroscopy of Photoinduced Electron Transfer in Dinuclear and Tetranuclear Fe/Co Prussian Blue Analogues

Abstract: The dynamics of photo-driven charge transfer-induced spin transition (CTIST) in two Fe/Co Prussian Blue Analogues (PBAs) is revealed by femtosecond IR and UV/vis pump-probe spectroscopy. Depending on temperature the known tetranuclear squaretype complex [Co2Fe2(CN)6(tp*)2(4,4'-dtbbpy)4](PF6)2 ( 1) exists in two electronic states. In acetonitrile solution at <240 K the low temperature (LT) phase is prevalent consisting of low-spin Fe(II) and low-spin Co(III), [Fe II LSCo III LS]2. Temperature rise causes therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…Studies on Fe-FePBA, [4] reported that just after photoexcitation, the electron is delocalised amongst six Fe ions surrounding the Fe III ion and that the following self-trapping of the CT state around one Fe ion is accompanied by damped oscillations,d ifferent from CN stretching modes,a nd assigned to low-frequencyl attice phonons.M ore recently,f emtosecond X-ray and optical absorption spectroscopies were used to study the CT process in ap hoto-excited Co III (S = 0)Fe II (S = 0) system. [1h] The element-specific XANES technique allowed for disentangling electronic and structural dynamics and revealed that it is the spin-transition, which is photoinduced first on the Co site within % 50 fs,t hat drives the subsequent Fe !Co chargetransfer within % 200 fs.Here again, the structural trapping of the Co II (S = 3/2)Fe II (S = 1/2) state,i sa ccompanied by coherent lattice vibrations.Z imara et al studied square-type complex [(Co III LS) 2 (Fe II LS) 2 ] [12] and concluded that as ingle electron transfer process takes place within % 400 fs on one of the Co À Fe pairs,t owards am etastable complex [Co III LS Fe II LS Co II HS Fe III LS ]. Thel ocal nature of the photoinduced CT was also reported for the Mn-FeP BA by Asahara et al, [13] by monitoring with optical pump-midinfrared probe technique the ultrafast dynamics of the photoinduced Mn III Fe II !…”
Section: Introductionmentioning
confidence: 99%
“…Studies on Fe-FePBA, [4] reported that just after photoexcitation, the electron is delocalised amongst six Fe ions surrounding the Fe III ion and that the following self-trapping of the CT state around one Fe ion is accompanied by damped oscillations,d ifferent from CN stretching modes,a nd assigned to low-frequencyl attice phonons.M ore recently,f emtosecond X-ray and optical absorption spectroscopies were used to study the CT process in ap hoto-excited Co III (S = 0)Fe II (S = 0) system. [1h] The element-specific XANES technique allowed for disentangling electronic and structural dynamics and revealed that it is the spin-transition, which is photoinduced first on the Co site within % 50 fs,t hat drives the subsequent Fe !Co chargetransfer within % 200 fs.Here again, the structural trapping of the Co II (S = 3/2)Fe II (S = 1/2) state,i sa ccompanied by coherent lattice vibrations.Z imara et al studied square-type complex [(Co III LS) 2 (Fe II LS) 2 ] [12] and concluded that as ingle electron transfer process takes place within % 400 fs on one of the Co À Fe pairs,t owards am etastable complex [Co III LS Fe II LS Co II HS Fe III LS ]. Thel ocal nature of the photoinduced CT was also reported for the Mn-FeP BA by Asahara et al, [13] by monitoring with optical pump-midinfrared probe technique the ultrafast dynamics of the photoinduced Mn III Fe II !…”
Section: Introductionmentioning
confidence: 99%
“…As mixed-valence compounds, Prussian Blue analogues (PBAs) have been used academically for the establishment of fundamental mixed-valent classifications related to the electronic coupling between the metal centers and the symmetry-allowed inner-sphere optical electron transfer occurring between them. 1 8 In reactivity aspects, these species have been utilized as cheap, metal-abundant catalysts in water oxidation processes 9 , 10 and electrochemical applications. 11 Recently, the use of these types of complexes in the development of photomagnetic switching materials has also been developed by several groups.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the general use of Prussian Blue as a resistant and fairly innocuous inorganic colorant cannot be overstated. As mixed-valence compounds, Prussian Blue analogues (PBAs) have been used academically for the establishment of fundamental mixed-valent classifications related to the electronic coupling between the metal centers and the symmetry-allowed inner-sphere optical electron transfer occurring between them. In reactivity aspects, these species have been utilized as cheap, metal-abundant catalysts in water oxidation processes , and electrochemical applications . Recently, the use of these types of complexes in the development of photomagnetic switching materials has also been developed by several groups. Furthermore, both anionic Prussian Blue and PBAs are also known to act as hosts for cationic guests in general, which has led to various applications. , Their use as sequestering agents has been explored, although their ion-exchange properties in aqueous solution are difficult to measure.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on Fe-FePBA, [4] reported that just after photoexcitation, the electron is delocalised amongst six Fe ions surrounding the Fe III ion and that the following self-trapping of the CT state around one Fe ion is accompanied by damped oscillations,d ifferent from CN stretching modes,a nd assigned to low-frequencyl attice phonons.M ore recently,f emtosecond X-ray and optical absorption spectroscopies were used to study the CT process in ap hoto-excited Co III (S = 0)Fe II (S = 0) system. [1h] The element-specific XANES technique allowed for disentangling electronic and structural dynamics and revealed that it is the spin-transition, which is photoinduced first on the Co site within % 50 fs,t hat drives the subsequent Fe !Co chargetransfer within % 200 fs.Here again, the structural trapping of the Co II (S = 3/2)Fe II (S = 1/2) state,i sa ccompanied by coherent lattice vibrations.Z imara et al studied square-type complex [(Co III LS) 2 (Fe II LS) 2 ] [12] and concluded that as ingle electron transfer process takes place within % 400 fs on one of the Co À Fe pairs,t owards am etastable complex [Co III LS Fe II LS Co II HS Fe III LS ]. Thel ocal nature of the photoinduced CT was also reported for the Mn-FeP BA by Asahara et al, [13] by monitoring with optical pump-midinfrared probe technique the ultrafast dynamics of the photoinduced Mn III Fe II !…”
Section: Introductionmentioning
confidence: 99%
“…Zimara et al. studied square‐type complex [(Co III LS) 2 (Fe II LS) 2 ] [12] and concluded that a single electron transfer process takes place within ≈400 fs on one of the Co−Fe pairs, towards a metastable complex [Co III LS Fe II LS Co II HS Fe III LS ].…”
Section: Introductionmentioning
confidence: 99%